2020
DOI: 10.1007/s00276-020-02552-1
|View full text |Cite
|
Sign up to set email alerts
|

The Kager’s fat pad radiological anatomy revised

Abstract: Purpose The aim of the study was to map connections within the Kager’s fat pad between the structures which limit it. Methods A retrospective re-review of 200 ankle magnetic resonance imaging (MRI) examination was conducted. Connections within the Kager’s fat pad between the superior peroneal retinaculum, the fibulotalocalcaneal ligament, the posterior talocalcaneal ligament, the flexor hallucis longus, the paratenon of the Achilles tendon, the flexor retinaculum and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…The IER, Eleni E. Drakonaki, Khaldun Ghali Gataa, Nektarios Solidakis, Paweł Szaro MRI (11) . The SPR connection to the calcaneofibular ligament and the Achilles paratenon was reported previously both in cadavers and MR imaging studies (12,21) . Other variations have been previously reported in cadavers, including the inferior due to its location, was found to serve as an intermediate station for connecting the SPR to the ATFL.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The IER, Eleni E. Drakonaki, Khaldun Ghali Gataa, Nektarios Solidakis, Paweł Szaro MRI (11) . The SPR connection to the calcaneofibular ligament and the Achilles paratenon was reported previously both in cadavers and MR imaging studies (12,21) . Other variations have been previously reported in cadavers, including the inferior due to its location, was found to serve as an intermediate station for connecting the SPR to the ATFL.…”
Section: Discussionsupporting
confidence: 62%
“…However, there is scarce evidence on the existence of these connections in MR studies. In a previous MR study, we documented SPR connections to the fibulotalocalcaneal ligament, the posterior talofibular ligament, and the flexor retinaculum via the fibulotalocalcaneal ligament (12) . The SPR-ATFL connection in that study was found in only 9% of cases, which is a lower proportion than in the current study.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previously proven connections between the lateral ligament complex of the ankle with ligaments in the Kager's fat pat may indicate the existence of some functional ligamentous-fascial units 28 where the ligament complex is one part of the entirety. The presence of interconnections between the lateral ankle ligaments explain the concomitant nature of lateral ankle ligament injuries, making them like the deltoid ligament or spring ligament complex; despite having parts, it is challenging to separate them from each other 10,29 .…”
Section: Discussionmentioning
confidence: 98%